(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The increased development challenges have been spreading everywhere and limiting the welfare of humanity on the earth around the globe. However, since 2015 the whole world has been moving towards a new global development agenda. This agenda is assumed to replace the millennium development goals (MDGs) that lapsed a few years ago (Atah, Nasr & Mohammed, 2018). This new global development plan aims to achieve 17 sustainable development goals (SDGs) by 2030. The recent inclination of international efforts has been directed towards utilizing all resources to create a sustainable world in which the present generation can meet their needs while preserving the rights of future generations. In other words, sustainable development requires economic growth that helps remove all the development challenges such as poverty, malnutrition, hunger, unemployment, illiteracy, etc. Alike, the complexity and fast growth of the social and environmental challenges that are treating human life economically and socially, communities are becoming more and more vulnerable to socio-economic issues and incapable of tackling them effectively. Moreover, since creating the development plan in 2015, countries worldwide are joining their efforts with combined bodies or agencies to achieve socio-economic sustainability and development by the year 2030. Recently, Islamic Social Finance has been underlined due to its financial inclusion role as one of the main drivers of sustainable development among academicians and specialists. Then, this paper aims to explore the main perspectives in which Islamic Social Finance plays a role in achieving SDGs. In this regard, the article discusses three main Islamic Social Finance tools: Zakat, Awqaf, and Infaq, and their potential to cover the global SDGs’ investment gap.